2004
DOI: 10.1002/net.10105
|View full text |Cite
|
Sign up to set email alerts
|

The generalized minimum spanning tree problem: Polyhedral analysis and branch‐and‐cut algorithm

Abstract: This article presents a branch-and-cut algorithm for the Generalized Minimum Spanning Tree Problem (GMSTP).Given an undirected graph whose vertex set is partitioned into clusters, the GMSTP consists of determining a minimum-cost tree including exactly one vertex per cluster. Applications of the GMSTP are encountered in telecommunications. An integer linear programming formulation is presented and new classes of valid inequalities are developed, several of which are proved to be facet-defining. A branch-and-cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…When all the prizes are equal to zero (or equivalently are exactly equal to each other within a node set in the partition), this problem corresponds to the generalized minimum spanning tree problem, that has been studied recently by several groups of researchers (see Feremans et al 2004;Golden et al 2005;Pop 2004). Since the GMST problem is NP-hard, it implies (by restriction) that the PCGMST problem is also NP-hard.…”
mentioning
confidence: 99%
“…When all the prizes are equal to zero (or equivalently are exactly equal to each other within a node set in the partition), this problem corresponds to the generalized minimum spanning tree problem, that has been studied recently by several groups of researchers (see Feremans et al 2004;Golden et al 2005;Pop 2004). Since the GMST problem is NP-hard, it implies (by restriction) that the PCGMST problem is also NP-hard.…”
mentioning
confidence: 99%
“…We remark that the odd cycle inequalities for the GMTSP, presented by Feremans et al [8], are the special case of the odd ring inequalities obtained when D = C. Moreover, it can be shown that the 'cycle' inequalities for the partial constraint satisfaction polytope, presented in Koster et al [12], are equivalent to odd ring inequalities, in the sense that the cycle and odd ring inequalities define the same facets of that polytope. The odd clique inequalities, on the other hand, appear to be entirely new.…”
mentioning
confidence: 71%
“…If |V k | > 1 and {v} is a cluster, then the SVUB is dominated by the cluster constraints x v = 1 and x(V k ) = 1, together with the VUBs y uv ≤ x u for all u ∈ V k . Now, Proposition 7 of [8] states that, in all other cases, the SVUB inequality defines a facet of the GMTSP polytope. The GMSTP polytope is contained in P(G), and has dimension |V | + |E| − m − 1, because it satisfies the equation y(E) = m − 1 in addition to the equations satisfied by P(G).…”
Section: Proposition 3 the Svubs (3) Define Facets Of P(g) Unlessmentioning
confidence: 99%
See 2 more Smart Citations